2020
DOI: 10.3390/ijerph17114047
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Ambient Ozone, PM2.5, and Meteorological Factors on COVID-19 Confirmed Cases and Deaths in Queens, New York

Abstract: The outbreak of coronavirus disease 2019 (COVID-19), caused by the virus SARS-CoV-2, has been rapidly increasing in the United States. Boroughs of New York City, including Queens county, turn out to be the epicenters of this infection. According to the data provided by the New York State Department of Health, most of the cases of new COVID-19 infections in New York City have been found in the Queens county where 42,023 people have tested positive, and 3221 people have died as of 20 April 2020. Person-to-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
176
4
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(197 citation statements)
references
References 37 publications
10
176
4
7
Order By: Relevance
“…Secondarily, part of the discrepancy could also be due to the probability family used for the response variable (Gaussian in Zhu et al, 2020;and in Li H et al, 2020;Poisson in Jiang et al, 2020). Adhikari et al (2020), who evaluated the influence between meteorological variables and air pollutants on the incidence and mortality from COVID-19, found that, among pollutants, daily maximum eight-hour ozone concentrations were significantly and positively associated with new confirmed cases related to COVID-19 (although not so PM 2.5 ). However, neither meteorological variables nor air pollutants showed significant associations with deaths related to COVID-19.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondarily, part of the discrepancy could also be due to the probability family used for the response variable (Gaussian in Zhu et al, 2020;and in Li H et al, 2020;Poisson in Jiang et al, 2020). Adhikari et al (2020), who evaluated the influence between meteorological variables and air pollutants on the incidence and mortality from COVID-19, found that, among pollutants, daily maximum eight-hour ozone concentrations were significantly and positively associated with new confirmed cases related to COVID-19 (although not so PM 2.5 ). However, neither meteorological variables nor air pollutants showed significant associations with deaths related to COVID-19.…”
Section: -Discussionmentioning
confidence: 99%
“…With regard to short-term (i.e. acute) exposure (measured as the temporal variation of air pollutants), Xu et al (2020) (in 33 locations in China), Zhu et al (2020) (in 120 cities in China), Jiang et al (2020) (3 cities in China), Li H et al (2020) (2 cities in China) and Adhikari et al (2020) (in Queens, New York) found significantly positive associations between the short-term exposure to air pollutants with newly confirmed cases. Furthermore, as Domingo et al (2020) point out, in a very recent review, the results of most of the studies suggest that the long-term exposure to air pollutants might lead to more severe and lethal forms of Most of the studies evaluating socioeconomic and demographic variables (four of the six studies) considered population density (Coccia, 2020;Ahmadi et al, 2020;Pequeno et al, 2020;and You et al 2020).…”
mentioning
confidence: 99%
“…Several observations report a significant association between ambient concentrations of PM 2.5 ( Adhikari and Yin, 2020 ; Bashir et al, 2020 ; Fattorini and Regoli, 2020 ; Frontera et al, 2020 ; Jiang et al, 2020 ; Li et al, 2020 ; Vasquez-Apestegui et al, 2020 ; Wu et al, 2020 ; Yao et al, 2020 ; Zhu et al, 2020 ; Zoran et al, 2020a ) and PM 10 ( Bashir et al, 2020 ; Coccia, 2020b ; Fattorini and Regoli, 2020 ; Jiang et al, 2020 ; Li et al, 2020 ; Yao et al, 2020 ; Zhu et al, 2020 ; Zoran et al, 2020a ) with COVID-19 pandemic across the most affected countries: China, Italy and U.S.A (see Table 1 ).…”
Section: Particulate Matter and Covid-19mentioning
confidence: 99%
“…Several studies have explored the association between SARS-CoV-2 transmission and the COVID-19 mortality rate with environmental factors, air pollution being among them [ 6 , 7 ]. In New York, which is the epicenter of the COVID-19 epidemic in the United States, it was observed that short-term exposure to ozone and other meteorological factors can influence SARS-CoV-2 transmission and susceptibility to infection, but was not associated with disease exacerbation and mortality, which seem to be dependent on other factors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%